Magnetic energy dissipation during the current quench of disruption in EAST. (October 2020) - Tang, T.; Zeng, L.; Chen, D. L.; Granetz, R. S.; Mao, S. T.; Duan, Y. M.; Zhang, L.; Zhuang, H. D.; Zhu, X.; Liu, H. Q.; Shen, B.; Jie, Y. X.; et al.
Abstract : A disruption database characterizing the current quench of disruptions with ITER-like tungsten divertor has been developed on EAST. It provides a large number of plasma parameters describing the predisruptive plasma, current quench time, eddy current, and mitigation by massive impurity injection, which shows that the current quench time strongly depends on magnetic energy and post-disruption electron temperature. Further, the energy balance and magnetic energy dissipation during the current quench phase has been well analysed. Magnetic energy is also demonstrated to be dissipated mainly by ohmic reheating and inductive coupling, and both of the two channels have great effects on current quench time. Also, massive gas injection is an efficient method to speed up the current quench and increase the fraction of impurity radiation.